Prof. Ilyas Muhammad Ali (1908–1991): An Analysis of His Intellectual History and Contributions to Hadith Studies in the Malay World - Jannatul Husna; Gamal Abdul Nasir Zakaria (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This article exploresthe intellectual history and contributions of Ilyas Muhammad Ali to hadith scholarship in the Malay-Indonesian archipelago. As an educator, mufti, and lecturer, he played pivotal roles in Islamic education, notably founding and developing IAIN Pekanbaru and IAIN Padang. However, scholarly research onhis biography and academic legacy remains limited among bothlocal and international researchers. Employing a qualitative methodology, this study utilizes documentary analysis and structured interviews. Primary data sources include his work, Durusal-Ahadithal-Nabawiyah(1939),as well astestimonies from family members and former students. Findings indicate that Ilyas made significant contributions to Islamic education in West Sumatra, Aceh, and Riau, particularly through his compilation of a forty-hadith collection designed as instructional material for Islamic secondary schools and the general public. The systematization of his compilation includes the hadith number, thematic title, textual transmission (matn), exegetical commentary, and pedagogical values. His Arba’in primarily addresses core Islamic ethical principles, spanning individual moral development to societal and civic life. Consequently, this study affirms that Ilyas’s scholarly output and intellectual contributions were instrumental in fostering ethical consciousness and moral character within Muslim society, guiding adherents toward virtuous conduct across diverse spheres of life.